Ultrahigh Density of Atomic CoFe-Electron Synergy in Noncontinuous Carbon Matrix for Highly Efficient Magnetic Wave Adsorption - Huang, Wenhuan; Qiu, Qiang; Yang, Xiufang; Zuo, Shouwei; Bai, Jianan; Zhang, Huabin; Pei, Ke; Che, Renchao (Nano-Micro Letters, 2022)
Improving the atom utilization of metals and clarifying the M–M’ interaction is both greatly significant in assembling high-performance ultra-light electromagnetic wave-absorbing materials. Herein, a high-temperature explosion strategy has been successfully applied to assemble the hierarchical porous carbon sponge with Co–Fe decoration via the pyrolysis of the energetic metal organic framework. The as-constructed hybrid displays a superior reflection loss (RL) value of − 57.7 dB and a specific RL value of − 192 dB mg−1 mm−1 at 12.08 GHz with a layer thickness of 2.0 mm (loading of 15 wt%). The off-axis electron hologram characterizes the highly distributed numerous polarized nanodomain variable capacitors, demonstrating the dipole and interfacial polarization along the edges of the nanopores. More importantly, the X-ray absorption spectroscopy analysis verifies the mutual interaction between the metal cluster and carbon matrix and the electronic coupling responsible for the greatly improved electromagnetic wave absorption. Highlights: 1 A typical 3D porous carbon sponge of CoFe@PCS exhibited the continuous distribution of nano-meso-micro-hierarchical pores in the range of 1 nm–15 μm. 2 The ultrahigh-density distribution of the nanoscale polarized charges (+ / −) along the edges of the pores resulted in nanoscale variable capacitors. 3 The high density of Co–Fe electromagnetic coupling on the carbon matrix, showing the enhanced electromagnetic wave attenuation.